Qualidade fisiológica e sanitária em sementes de cultivares de Phaseolus lunatus L. - Nascimento, Maria das Graças Rodrigues do (2015)
The need for more detailed information on traditional cultures of the northeast region is essential for their development by family farmers. Thus the objective of this work was to evaluate the physiological and sanitary quality of seeds of lima bean cultivars (Phaseolus lunatus L). The work was conducted in the Seed Analysis Laboratory and Pathology of the Center of the Federal University of Paraíba Agricultural Sciences, with seeds of cultivars Branca, Cearence, Orelha de Vó, Rosinha and Roxinha, which was divided into four stages: the I experiment seeds were submitted to salt stress condition using as solute sodium chloride (NaCl) in 0.0 concentrations (control); 1.5; 3.0; 4.5, 6.0, 7.5 and 9.0 dS m-1 at different constant temperatures of 25, 30 and 35 °C. In the second experiment the seeds were submitted to water stress simulated by polyethylene glycol solutions 6000 (PEG 6000) at concentrations of 0.0; -0.2; -0.4; -0.6; -0.8; -1.0 And -1.2 MPa and temperatures of 25, 30 and 35 ° C. In the experiment III germination tests were carried out, emergency and tetrazolium tests and electrical conductivity to evaluate the quality of the seeds, as in the experiment IV held a survey and identification of the main pathogens in seeds by the method of "blotter test". In assessing the effect of the treatments of the experiments I, II, IV germination and vigor tests were performed (first count, germination speed index, length and seedling dry matter). Germination of lima bean cultivars is high when subjected to salt concentrations of up to 9 dS m -1 ; the seeds of the cultivar Roxinha are more tolerant to saline with sodium chloride; at 35 ° C does not favor the development of seedlings in saline conditions for all cultivars. The seeds of the cultivar Orelha de Vó are more sensitive to water stress, germinating only to the potential -0,6MPa; the seeds of the cultivar Rosinha are more tolerant to drought stress induced by PEG 6000 during germination and early seedling development; the length and seedling dry weight of lima bean cultivars are negatively affected when the seeds are subjected to osmotic potential from -0.2 MPa. The seeds of the cultivar Roxinha are better physiological quality and the worst quality Cearence; the tetrazolium test is recommended in the evaluation of seed lima bean cultivars; the electrical conductivity test is not recommended to evaluate the seeds of cultivars lima bean. Fungal genera most frequent in the seeds of lima bean cultivars are Aspergillus, Fusarium, Penicillium and Cladosporium; the seeds of the cultivar Cearence are those with lower germination and higher incidence of Fusarium fungi; the physiological quality of seeds of the variety Roxinha was the best compared to Cearence in all variables.